Isochrysis maritima Billard and Gayral Isolated from Penang National Park Coastal Waters as a Potential Microalgae for Aquaculture - Mohammad Basri Eshak; Wan Maznah Wan Omar (Tropical Life Sciences Research, 2017)
The importance of polyunsaturated fatty acid (PUFA) in microalgae was widely reported. In this study, six isolated microalgae from Teluk Aling, Penang National Park were screened for PUFA contents. Isochrysis maritima showed the best polyunsaturated fatty acids essential for aquaculture species compared to other microalgal species tested. This species is a good choice as aquaculture feed due to its small size (3 – 7 ?m), which is appropriate size for ingestion. The maximum specific growth rate of this species was also high (0.52–0.82 days-1) and comparable with many recognized aquaculture microalgae. On the other hand, this species was also able to be cultivated successfully in big volume (1000 L culture medium) with open hatchery condition, which will optimize the production cost. Low ratio of omega-6 to omega-3 essential fatty acids (EFA) recorded in I. maritima at any growth phases (0.32 - 0.45) also indicate optimal values for feeding. Kepentingan asid lemak poli tak tepu (PUFA) dalam mikroalga telah dilaporkan secara meluas. Dalam kajian ini, enam mikroalga yang diasingkan dari Teluk Aling, Taman Negara Pulau Pinang telah disaring untuk kandungan PUFA. Isochrysis maritima menunjukkan bacaan asid lemak poli tak tepu yang terbaik yang penting untuk spesies akuakultur berbanding spesis microalga lain yang diuji. Spesis ini adalah pilihan yang baik sebagai pemakanan akuakultur kerana saiz yang kecil (3-7 ?m), iaitu saiz yang sesuai untuk pemakanan. Kadar maksimum pertumbuhan spesifik spesis ini juga tinggi (0.52 – 0.82 hari-1) dan setanding dengan kebanyakan mikroalga akuakultur yang telah diiktiraf. Selain itu, spesies ini juga boleh dikultur dengan jayanya dalam skala yang besar (1000 L media kultur) di tempat penetasan yang terbuka, yang akan mengoptimumkan kos pengeluaran. Nisbah omega-6 kepada omega-3 asid lemak (EFA) yang rendah dicatatkan pada I. maritima pada mana-mana fasa pertumbuhan (0.32 - 0.45) juga menunjukkan nilai yang optima sebagai makanan akuakultur.